More and better rights? Some considerations - Corvalán, Alejandro; Soto, Francisco (Política. Revista de Ciencia Política, 2020)
Economic, social, and cultural rights are the primary citizen demand in the Chilean constitutional process. This paper discusses some relevant issues that must be considered by the Constitutional Convention when creating the catalog of rights regulated by our new constitution. First, we analyze the evolution of rights in the world. Second, we evaluate the economic consequences of rights catalogs. Third, we place the Chilean rights system in the international context.